Stereoselective Four-Component Synthesis of Functionalized 2,3-Dihydro-4-Nitropyrroles - Wang, Dong; Ma, Xinyue; Dong, Linru; Feng, Hairong; Yu, Peng; Désaubry, Laurent (Frontiers in Chemistry, 2019)
We report a metal-free and stereoselective four-component reaction between α-ketoamides, amines, aromatic aldehydes and β-nitroalkenes or β-pivaloxy-nitroalkanes to obtain 2,3-dihydro-4-nitropyrroles functionalized in every position. Notably, the utility of this method was demonstrated with the efficient construction of pharmaceutically relevant products.